IMPLEMENTATION OF THE EXAMPLES-NOT-EXAMPLES METHOD TO INCREASE STUDENT LEARNING CREATIVITY - Arfandi Arfandi; Agus Supriyadi; Maulida Arifatul Hasanah (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2022)
Developing the relationships with students during teaching and learning was by the teaching method. As a result, teaching approaches made a significant contribution to teaching and learning activities. Learning examples that are not examples was one example of a media-based learning methodology. The media in learning was our problem in the teaching and learning process because the media was the component that will give an effect on student learning outcomes because learning messages can be delivered according to the learning objectives through media. To maximize learning and teaching effectiveness, pay attention to how learning messages were arranged so that students were engaged in learning. This research had two objectives: (1) How does the Examples-Non-Examples technique in fiqh at MI Salafiyah Syafi'iyah Sukorejo Banyuputih Situbondo work? (2) Can the Examples-Non-Examples technique be used to boost students' learning creativity in Fiqh at Salafiyah Syafi'iyah, Sukorejo Banyuputih, and Situbondo? The classroom action research approach was used with two cycles to get a good result. Before doing research utilizing the examples-without-examples technique, the researcher conducted an initial test (pre-test) in the pre-cycle, whereas in cycles I and 2, one meeting was held with a time allocation of 1 x 40 minutes. The research findings were acquired in four stages: planning, execution, observation, and reflection. For the findings: (1) The example-non-examples approach was successfully used. This can be observed in the percentage scores of research activities and student activities, which climbed each cycle after adopting the Example-Non-Examples technique in cycle I, which began at 66% and increased to 75%. Student participation in cycle II grew from 62% to 81%. (2) When the Examples-Non-Examples approach was used, student learning creativity rises. This appears in the pre-test, where the proportion of learning completion was 14%, it increased to 45% in the post-test cycle I, and 93% in the post-test cycle II.